Application of Individual Counselling with Attending, Silence, and Giving Advice Techniques in Reducing AuthoPhobia in Students - Gumiandari, Septi; Setiani, Yani (Yayasan Minang Darussalam, 2023)
The lack of counselling conducted at SMA Negeri 1 Pasawahan has had an impact on the level of anxiety for students in carrying out daily activities. Therefore, it is necessary to take action to help students who experience anxiety/fear so that they are more confident. This study aims to find out about the level and attitude of authoPhobia experienced by students, then to find out about the implementation of individual counselling using Attending, silence, and giving advice techniques carried out on people with authoPhobia then to find out the effectiveness of the implementation of individual counselling using Attending, Silence, and giving advice techniques in reducing authoPhobic attitudes. This research method uses a qualitative approach with research subjects of a number of SMA Negeri 1 Pasawahan students who experience authophobia. Research data were collected through interview and observation techniques using a 10-question questionnaire to 12 students. The results showed that the application of individual counselling with Attending, silence, and giving advice techniques was effective in reducing authophobic attitudes in SMA Negeri 1 Pasawahan students. Students experienced an increased understanding of the attitudes that must be taken in fighting the phobia and felt more comfortable to talk about their fears. In addition, they also gained strategies and skills to manage the anxiety that arises due to authophobic attitudes.